Cardiopulmonary bypass, temperature, and central nervous system dysfunction - McLean, R F; Wong, B I; Naylor, C D; Snow, W G; Harrington, E M; Gawel, M; Fremes, S E (Circulation (New York, N.Y.), 1994)
Neurological injury is an important cause of morbidity and mortality after cardiac surgery. With the advent of warm heart surgery, the neuroprotective role of hypothermic cardiopulmonary bypass (CPB) has come under increasing scrutiny. Preliminary work by us in the area found no increased risk of neurological morbidity with normothermic CPB in a small group of patients and suggested a possible benefit. The purpose of the present study is to compare the incidence of neurological and neuropsychological dysfunction in a larger number of patients randomized to warm or cold aortocoronary bypass surgery. With the approval of the institutional research ethics committee, 201 aortocoronary bypass patients were randomized to normothermic or moderate hypothermic CPB and subjected to neurological and neuropsychological evaluation. These subjects were a subset of patients enrolled in a large multicenter trial comparing warm versus cold heart surgery. The examinations took place preoperatively, 5 days after operation, and a 3-month follow-up. The examination consisted of a clinical neurological examination and a brief neuropsychological test battery. The neuropsychological tests included the Buschke selective reminding procedure, the Wechsler memory scale-revised visual reproduction subtest, the trial making test (parts A and B), the Wechsler adult intelligence scale-revised digit symbol subtest, and the grooved pegboard test. The examiner and subjects were unaware of the CPB temperature allocation (warm, > 34 degrees C; cold, < or = 28 degrees C). Statistical analysis was performed using the SAS statistical software package. Two hundred one patients were enrolled in the study. Of these, 155 patients completed the entire protocol and were included in the final analysis (warm group, n = 78; cold group, n = 77). One patient in the warm group died perioperatively from a massive hemispheric stroke. Another warm group patient was unable to complete neuropsychological evaluation because of a perioperative stroke. Thus, 153 patients completed the entire series of neuropsychological tests. A total of 6 patients (warm group, n = 2; cold group, n = 4; P = NS) suffered from perioperative focal neurological deficits. There was a consistent deterioration in scores from tests of psychomotor speed/coordination (trial making, digit symbol, pegboard) in the early postoperative period, which resolved by the 3-month follow-up. Tests of memory (Buschke, Wechsler memory scale) showed no evidence of patient deterioration in the postoperative period. No difference was seen between the warm and cold groups. In this randomized trial of normothermic versus hypothermic CPB, we found deterioration in scores of tests of psychomotor speed but not of memory in the early postoperative period. We were unable to demonstrate any neuroprotective effect from moderate hypothermia in this patient population.